Magnesium-Impregnated Biochar for the Removal of Total Phosphorous from Artificial Human Urine - Fariha Mohd Idrus, Nurul; Ain Jamion, NurulÂ´; Omar, Qistina; Ahmad Izaddin Sheikh Md Ghazali, Sheikh; Abdul Majid, Zaiton; Kong Yong, Soon (International Journal of Engineering and Technology, 2018)
Biochar has an alkaline and porous structure that could be a potential material for recycling phosphorous (P) from urine. Sawdust (SD) was pyrolyzed to produce sawdust biochar (SDB), and then impregnated with magnesium (Mg) to produce Mg-impregnated biochar (SDBM). Artificial human urine (AHU) solution was used for a batch sorption study, and various sorption parameters (i.e., sorbent/solution ratio, pH of AHU, and initial total P concentration of AHU) were optimized. The concentration of total P was measured using an inductively coupled plasma-optical emission spectroscopy (ICP-OES). The surface morphology and elemental analysis for SDB, SDBM and the struvite-loaded SDBM (SMSDB) were investigated using scanning electron spectroscopy-energy dispersive x-ray spectroscopy (SEM-EDX). The total P sorption capacity for SDBM (32755 mg/g) was higher than that of SDB (7782 mg/g) and SD (10682 mg/g). The optimum total P removal for SDBM (21.2%) was achieved at a sorbent/solution ratio of 0.06g/L at pH 9. Sorption of total P may have occurred on the heterogeneous surface of SDBM. The presence of struvite crystals indicates that phosphate was adsorbed and then precipitated on the surface of SDBM.Â Â Â